2020
DOI: 10.1007/s00705-020-04863-5
|View full text |Cite
|
Sign up to set email alerts
|

Deformed wing virus prevalence and load in honeybees in South Africa

Abstract: Deformed wing virus (DWV) is an emerging honeybee pathogen that has appeared across the globe in the past 40 years. When transmitted by the parasitic varroa mite, it has been associated with the collapse of millions of colonies throughout the Northern Hemisphere. However, despite the presence of the mite in the Southern Hemisphere, infested colonies survive. This study investigated the prevalence of DWV genotypes A, B and C along with their viral loads in South Africa and compared the findings with recent data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…Ultimately, this study has shown that since 2010 when DWV-B was not detected, the viral load and prevalence of DWV-B have increased to the point at which DWV-B now dominates colonies found on Big Island and co-dominates with DWV-A on Oahu. Thus far, this increase in DWV-B fits with what has been observed in numerous other regions ( Figure 2 ) [ 16 , 20 , 30 ]. We know that DWV-B replicates to greater titers than DWV-A when injected into pupae [ 47 , 48 ] whilst being equally [ 48 ] or less virulent [ 49 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Ultimately, this study has shown that since 2010 when DWV-B was not detected, the viral load and prevalence of DWV-B have increased to the point at which DWV-B now dominates colonies found on Big Island and co-dominates with DWV-A on Oahu. Thus far, this increase in DWV-B fits with what has been observed in numerous other regions ( Figure 2 ) [ 16 , 20 , 30 ]. We know that DWV-B replicates to greater titers than DWV-A when injected into pupae [ 47 , 48 ] whilst being equally [ 48 ] or less virulent [ 49 ].…”
Section: Discussionsupporting
confidence: 88%
“…as other studies using the same methodology have found a reduced DWV burden in resistant, not treated, managed populations in South Africa and Brazil [30]. [9], 2012 [29], 2012 * [17], 2015/16 [26] and 2019 (this study).…”
Section: Figuresupporting
confidence: 74%
See 3 more Smart Citations